Assessment of Planning Practices among Midwife Managers in Healthcare Facilities in Umuahia North Local Government Area. A Descriptive Quantitative Study. - Ogbonna-Adiele, Chituru; Abigail Horsfall (Student's Journal of Health Research, 2022)
Background: The susceptibility to ill health increases daily as a result of social and economic crises. Women and children are mostly affected by an increased rate of morbidity and mortality. Midwife managers have major roles to play in providing high-quality care to these patients. Therefore, midwife managers have to engage in effective planning to be competent and effective. The study aims to assess the planning practices among midwife managers. Methodology ; A Descriptive quantitative design was used for the study. A systematic sampling technique was used to select 180 respondents from two hospitals. A semi-structured questionnaire of the Likert scale was used to elicit information from the respondents. Data were analyzed using a statistical package for social science and were presented in distribution and percentage tables. Results : It was discovered that the majority of the midwife managers were female, within the age bracket of 31-40years, and were in the antenatal ward. 35.56% of the midwife managers practiced strategic planning while contingency type of planning was least practiced (17.22%). 47.22% of the midwife managers had in-depth knowledge of planning practices and engage in the weekly plan. The researcher observed that the extent to which midwife managers engage in planning practices depends on how much they know about the concept. Conclusion : Midwife managers are essential stakeholders in providing evidence-based practice and so should engage in effective planning. Recommendation : It is recommended that midwife managers should be empowered to improve their planning practices through training, workshops, and mentorship.